2019
DOI: 10.1111/1756-185x.13520
|View full text |Cite
|
Sign up to set email alerts
|

microRNA involvement in the regulation of survivin in peripheral blood mononuclear cells from rheumatoid arthritis patients

Abstract: Aim Impaired regulation of immune tolerance results in autoimmune diseases, such as rheumatoid arthritis (RA). Survivin is an anti‐apoptotic protein and can induce cellular mitosis. In the current study, we assessed the transcript level of total survivin (survivin‐TS) and its three major variants and evaluated the expression level of important micro RNAs (miRNAs) involved in survivin expression regulation in RA patients. Method Peripheral blood mononuclear cells (PBMCs) were isolated from 50 healthy controls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The implication of survivin in RA pathogenesis has been established. It is substantiated by the upregulation of survivin in serum ( 77 ), synovial fluid ( 50 ), and peripheral blood mononuclear cells (PBMCs) ( 7 ) of RA patients, underpinning its potential relevance as a diagnostic biomarker and prognostic indicator in these patients ( 78 , 79 ). It is evidenced further by research that found elevated survivin expression in patients with juvenile idiopathic arthritis to contribute to polyarticular involvement and systemic disease progression ( 80 ).…”
Section: Irregular Expression Of Survivin-specific Micrornas In Speci...mentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of survivin in RA pathogenesis has been established. It is substantiated by the upregulation of survivin in serum ( 77 ), synovial fluid ( 50 ), and peripheral blood mononuclear cells (PBMCs) ( 7 ) of RA patients, underpinning its potential relevance as a diagnostic biomarker and prognostic indicator in these patients ( 78 , 79 ). It is evidenced further by research that found elevated survivin expression in patients with juvenile idiopathic arthritis to contribute to polyarticular involvement and systemic disease progression ( 80 ).…”
Section: Irregular Expression Of Survivin-specific Micrornas In Speci...mentioning
confidence: 99%
“…Upregulated survivin expression in autoreactive immune cells from patients with various autoimmune diseases has been evidenced in this context. Further investigation into the regulatory pathways of survivin mRNA in these cells has shown the emerging role of survivin-targeting miRNAs in the maintenance of autoreactivity ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…BIRC5 is a new member of the apoptosis inhibitory protein family and is the most potent inhibitor of apoptosis. BIRC5 has complex biological functions, inhibits apoptosis, promotes cell transformation and participates in cell mitosis, angiogenesis and drug resistance (Ebrahimiyan et al., 2019). It was reported that the expression level of BIRC5 was significantly higher in NSCLC tissues compared to non-tumor tissues, and negatively correlated with Tp53 (Wang et al., 2018; Vayshlya et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars hold the opposite view. It has been shown that miR-34a expression was up-regulated in PBMCs from RA patients ( Ebrahimiyan et al, 2019 ; Xie et al, 2019 ), and silencing miR-34a markedly reduced release of inflammatory mediators ( Kurowska-Stolarska et al, 2017 ). In other autoimmune diseases, such as Sjögren Syndrome, the level of miR-34a was also significantly elevated in patients ( Kim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%